DEM simulation of the pullout behavior of geogrid-stabilized ballast with the optimization of the coordination between aperture size and particle diameter. (20th September 2020) - Miao, Chenxi; Jia, Yafei; Zhang, Jun; Zhao, Jianbin
Highlights: The interaction mode between geogrid and ballast is not affected by particle size. Coarser ballasts generally give more considerable elastic potential energy. The optimum ratio of triaxial geogrid aperture size to ballast size is 1.557. Triaxial and biaxial geogrids are similar in picking the optimal ballast size. Abstract: Based on the well-established constitutive models and particular configurations used in the discrete element method (DEM) simulation of the geogrid-stabilized ballast system, this paper presents the pull-out behavior of a triangular geogrid embedded in ballast under special consideration of the particle size. A representative particle size that equals to the diameter of the inscribed circle of the triangular aperture was selected to visualize the axial force distribution and the interface responses regarding the contact force. Meanwhile, fabric anisotropy on the normal component of contact force was introduced to explain the development of macroscopic strength. Results show that the first transverse rib makes the most contribution to the pull-out force. The V-shaped strong contact force chains were mainly grown in the geogrid-ballast substantial interaction region R1, and this interaction mode is not affected by particle size. Moreover, the maximum number of particles trapped in an aperture, Nmax, is used as the quantized indicator for numerical pull-out tests on 6 controlled conditions, and results unveil that the optimal reinforcement can be achieved when Nmax  = 2, by evaluating the pull-out resistance, the interlocking effect, the energy dissipation, and the volumetric response.